ANALISIS KECELAKAAN LALU LINTAS (STUDI KASUS - JALAN RAYA UNGARAN - BAWEN) - Dendy Wicaksono; Rizky Akbar Fathurochman; Bambang Riyanto; YI. Wicaksono (Jurnal Karya Teknik Sipil, 2014)
Traffic accidents are a serious problem that requires treatment given the magnitude of the resulting losses. For this study needs to be done is conducting an analysis of the data kecelakaaan existing traffic. This final project took place Unggaran Highway Toll - Bawen in Semarang Regency. The roads are arterial roads are congested with traffic. This is due to the road connecting Semarang as one of the major cities in Central Java with the surrounding areas, for example : Solo, Magelang and Yogyakarta. The purpose of this study was to identify the location and cause of road accidents in order to provide suggestions efforts to reduce accidents will happen. Analysis of the data by the author to determine the relationship between variables that affect the number of accidents using SPSS computer program, while for determining the location of the accident - prone (blackspot), using statistical techniques of traffic control. Incidence of traffic accidents are caused by several factors, namely human (driver), environment, vehicle and road. From the data analysis, humans are the main factors causing accidents (66.89%). Driver is less anticipated driver behavior most often cause accidents (72.45%). The most frequent type of accident happens is hit the front - front (50.85%), with motorcycles (53.78%) as the most frequent vehicles involved. The most frequent time of an accident is at 12:00 to 18:00 (31.74%), and professional drivers who are often involved in accidents are employees / private (61.86%). Location blackspots on roads Unggaran - Bawen have 6, which Pertigaan Citroen (40 events), Pertigaan Weak Abang (35) events, Pertigaan Ngobo ( 31 events), Home of PT Sosro = (27 events), Home of PT Apac Inti Corpora (32 events), Pertigaan Bawen (36 events) Accident that occurred on Jalan Raya Unggaran - Bawen in the next 5 years (2008-2012) is as much 293 events and 201 events which occurred at the point - titk blackspot, while the rest occurred with locations spread along roads Unggaran - Bawen. Details of the total casualties are 444 people minor injuries (72.55%), 78 people were seriously injured (12.75%), and 90 people died (14.71%). Based on the data and the field conditions we have several recommendations to reduce the rate of accidents on roads Unggaran - Bawen ie : need to be made to the guardrail or median openings at the intersection with the aim of anticipating the next hit-and - forward, need to manufacture lap behind (U - Turn) on roads Unggaran - Bawen to facilitate vehicle that will turn it over, the need for enlargement of the fingers - fingers curved corner at the intersection, thereby reducing the frontal crash and will expand the driver's view when cornering at intersections, the need for the provision of counseling about driving safety, the need for the creation of a study conducted motorcycle lanes on Jalan Raya Unggaran-Bawen.